Refurbishing, Extending, Recreating, and Renewing the Boole Library at University College Cork, Ireland - McMahon, Seamus (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
This paper reports on the new Postgraduate Research Library Project at Cork using it as a case study to consider the building and design issues which arise from a reconfiguration and extension of an existing building. It will also reflect on the experience of working with joint architects from different continents; SBRA of Boston, USA, and Wilson Architecture of Cork, Ireland. It reports on the key objectives and features of the new spaces including the various consultation and decision-making processes with the Design Team, library staff, and other stakeholders during the project. It concludes with a consideration of lessons learnt.